The development and standardisation of a test of hearing for telephone operators - Raju Ananth (Journal of All India Institute of Speech and Hearing)
The Government of India had indicated to the All India Instjtute of Speech and Hearing, to dev;develop standardized tests for fixing th levels of hearing wnich is essential for a telephone operator to perform his duty efficiently. The problem becomes more acute when a telephone operator, who is already appointed dev010ps a h·.Iaring problem. Even during recruitment, no standardised h aring test has been specified by the Government to judge the hearing fficiency of the applican"ts in terms of telephone speech in trunk exchange environments